Pirogoff amputation for foot osteomyelitis: a case report and review of literature - Late, Sudhir Gajanan; Padalkar, Pravin Pandurang; Patil, Abhishek Vinayak; Gadge, Sudhir Gangaram (International Journal of Research in Orthopaedics, 2026)
Deciding the level of amputation is influenced by healing potential of the stump and preservation of the limb length to optimise the mobility and energy requirement for walking. In 1854, the Russian surgeon Nikolay Ivanovich Pirogoff introduced a technique of foot amputation in which the heel is preserved and used as a base. The forefoot, midfoot, talus, distal part of the calcaneus, and distal tibial articular cartilage are removed. The plantar skin flap is left attached to the calcaneus, which is rotated 90 dorsally to create a sensate weight-bearing surface with minimal loss of leg length. Since the intact heel pad creates the plantar aspect of the stump, the patient is able to bear full weight on the limb, after bone-healing has occurred, with or without a prosthesis. We present a case of a patient who underwent an amputation with the Pirogoff technique following a traumatic compound Lisfranc’s injury and subsequent its progression to osteomyelitis of forefoot and midfoot. Eight months after the procedure, the patient was able to bear weight on the left lower extremity and was fitted with a definitive prosthesis with a long silicon liner. She was able to walk without pain or the aid of crutches. The rating according to the 100-point Taniguchi scale was 75 points, which indicated a very good result. This case adds to the body of evidence supporting the Pirogoff amputation as a valuable reconstructive option in challenging post traumatic severe forefoot injuries with osteomyelitis. The patient was informed and duly consented for publication of the data.